A review of the Euphorbia schinzii-complex (Euphorbiaceae) in southern Africa - Bruyns, Peter V.; Klak, Cornelia; Hanáček, Pavel (Phytotaxa, 2020)
The species closely related to Euphorbia schinzii in subg. Euphorbia are reviewed for southern Africa. Two new species, E. pisima and E. steelpoortensis are described that are closely related to E. lydenburgensis. Euphorbia complexa is reduced to synonymy under E. schinzii. One new subspecies, E. schinzii subsp. schinzioides, is described for E. schinzii, while E. limpopoana is reduced once again to subspecific level, this time under E. schinzii as E. schinzii subsp. bechuanica. Euphorbia schinzii then has three subspecies. The concept of E. clivicola is extended to include collections from a much wider area than before. A new subspecies, E. clivicola subsp. calcritica, is described for E. clivicola. Euphorbia subsalsa subsp. fluvialis is more closely related to E. otjipembana than to E. subsalsa and consequently is changed to E. otjipembana subsp. fluvialis.